Uncertainty analysis of climate change impacts on runoff. - Galavi, Hadi; Lee, Teang Shui (2012)
Warming of the atmosphere observed over several decades is associated with the changes occurring in hydrological systems. These changes include precipitation patterns and extremes; the amount and generation of river flow; the frequency and intensity of flood and drought; and, by extension, the quantity and quality of freshwater resources [1]. To study the climate changes, General Circulation Models (GCM) are repeatedly stated as the main tools to assess the changes. In water resources studies, hydrological models are mainly used to quantify the hydrological effects of climate change using GCM simulations as input [2]. However, the spatial resolution mismatch between GCMs outputs and the data requirements of hydrological models constitutes a major obstacle in impact studies [3]. Along with the uncertainties associated with GCMs, Greenhouse Gases Emissions Scenarios uncertainty has also been treated as a structural uncertainty. To date, there has been a little discussion on the influence of uncertainties related to the downscaling methods [4] and hydrological models [5] on the magnitude of driven uncertainty of impact studies. This article reviews recent advancements in the uncertainty analysis and modeling of the climate change impacts and propose a strategy for integration of all sources of uncertainty and in this regard to provide a comprehensive climate change uncertainty model.